Optimizing activity of herbicides at reduced rate on Emex spinosa campd. with adjuvants - Javaid,M.M. (2012)
In pot experiments, two adjuvants were evaluated for their efficacy in enhancing activity of five herbicides applied at reduced rates (75% of the recommended rates) on Emex spinosa at the cotyledon-leaf and at the two- to four- leaf stage. Herbicides (at recommended rates) including fluroxypyr+MCPA at 450 g a.i. ha-1, carfentrazone-ethyl at 20 g a.i. ha-1, bromoxynil+MCPA at 450 g a.i. ha-1, thifensulfuron-methyl at 75 g a.i. ha-1 and tribenuronmethyl at 75 g a.i. ha-1 alone and tank mixed at reduced rates with adjuvants, namely, alkyl ether sulphate sodium salt at 625 mL ha-1 or fatty alcohol ethoxylate at 375 mL ha-1. Addition of the adjuvants to reduced rates of fluroxypyr+MCPA and carfentrazone-ethyl, increased their efficacy with 100% mortality and biomass reduction of E. spinosa at the cotyledon- leaf stage and at the two- to four- leaf stage which was similar to their recommended rates without the adjuvants except for carfentrazone-ethyl at a reduced rate without adjuvants at the two- to four- leaf stage. Bromoxynil+MCPA at reduced rates with alkyl ether sulphate sodium salt also gave 100% control of E. spinosa over weedy check at the two- to four- leaf stage. Both the adjuvants generally increased the efficacy of tribenuron-methyl at reduced rates when sprayed at both leaf stages. These findings suggest that the use of adjuvants may increase the efficacy of the above mentioned herbicides against E. spinosa and it may be incorporated in an integrated weed management program.